ANALISIS PENGARUH PENERAPAN SISTEM INFORMASI KEUANGAN DAERAH (SIKD) TERHADAP PEMROSESAN SURAT PERTANGGUNGJAWABAN (SPJ) BELANJA DI DINAS PERINDUSTRIAN DAN PERDAGANGAN KABUPATEN SLEMAN - Martika Khoirun Nisa; Agung Slamet Prasetyo; Priyastiwi (LPPM PoliteknikPratamaKendal- Universitas Sains Dan Teknologi Komputer, 2025)
This research aims to analyze the influence of SIKD Sleman on SPJ-shopping processing at the Sleman Industry and Trade Department. The research method used is qualitative with primary and secondary data sources. Primary data was obtained directly through interviews, while secondary data was obtained by analyzing independently by reading the relevant laws and regulations. Based on the results of research in the form of interviews and literature studies, it can be concluded that the use of the Sleman SIKD has an influence on SPJ-shopping processing at the Regency Industry and Trade Department. The use of SIKD makes SPJ-shopping processing faster and easier so that annual budget absorption can be maximized.